2011
DOI: 10.1590/s0006-87052011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Espaçamento e densidade de semeadura para cultivares de sorgo granífero no semiárido

Abstract: Como existem poucas informações sobre o manejo cultural do sorgo em regiões do semiárido, neste trabalho foram instalados dois experimentos, avaliando-se três densidades de plantas e três espaçamentos de cultivares de sorgo granífero, em dois anos agrícolas, na Região Norte do Estado de Minas Gerais. Em cada ano foram instalados experimentos em áreas contíguas, adotando-se, respectivamente, os espaçamentos entre linhas de 50 cm, 70 cm e 90 cm e no outro experimento foram avaliadas três densidades de semeadura,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
(2 reference statements)
1
9
0
8
Order By: Relevance
“…Reduction caused by water stress were also observed by Menezes et al (2015), who found reductions of 39% in grain sorghum lines and by Batista et al (2017), who found reductions of 35 and 65% in two years of evaluation in grain sorghum hybrids. Albuquerque et al (2011) evaluated sorghum cultivars in a semiarid region, obtaining an average yield of 1,710 kg ha -1 under low rainfall and 5,090 kg ha -1 under good rainfall conditions. Sorghum is a cereal tolerant to drought, when compared to maize and wheat, but when it is exposed to intense water deficit, mainly during flowering, grain yield is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction caused by water stress were also observed by Menezes et al (2015), who found reductions of 39% in grain sorghum lines and by Batista et al (2017), who found reductions of 35 and 65% in two years of evaluation in grain sorghum hybrids. Albuquerque et al (2011) evaluated sorghum cultivars in a semiarid region, obtaining an average yield of 1,710 kg ha -1 under low rainfall and 5,090 kg ha -1 under good rainfall conditions. Sorghum is a cereal tolerant to drought, when compared to maize and wheat, but when it is exposed to intense water deficit, mainly during flowering, grain yield is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal arrangement of plants permits efficient exposure to solar radiation, soil nutrients, and water (Albuquerque et al, 2011b). During visits to the properties, we noted that the producers used high seeding rates, which may compromise the development of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…O manejo da cultura afeta sua produtividade, com a redução dos espaçamentos entre fileiras promoveram-se incrementos na produtividade de grãos e panículas do sorgo granífero, independentemente da população de plantas e cultivar avaliado (Albuquerque et al, 2011 (Leão et al, 2011).…”
Section: Fundamentação Teóricaunclassified
“…O sorgo (Sorghum bicolor L. Moench) é uma cultura alternativa às culturas tradicionais como o milho, sendo uma planta xerofílica e com baixa exigência nutricional, se adapta a ambientes com estresse hídrico e salinidade; podendo ser usado na alimentação humana, animal (grãos e forragem) e produção de açúcar (Albuquerque et al, 2011;Feijão et al, 2011;Cysne e Pitombeira, 2012;Souza et al, 2012;Moraes et al, 2013).…”
unclassified